2015
DOI: 10.1111/ele.12541
|View full text |Cite
|
Sign up to set email alerts
|

Temperature driven changes in the diet preference of omnivorous copepods: no more meat when it's hot?

Abstract: Herbivory is more prevalent in the tropics than at higher latitudes. If differences in ambient temperature are the direct cause for this phenomenon, then the same pattern should be visible in a seasonal gradient, as well as in experiments manipulating temperature. Using (15)N stable isotope analyses of natural populations of the copepod Temora longicornis we indeed observed seasonal differences in the trophic level of the copepod and a decrease in trophic level with increasing temperature. In a grazing experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
114
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(120 citation statements)
references
References 49 publications
5
114
0
1
Order By: Relevance
“…We tested consumption rates and diet selection at three temperatures (15-25°C) which may be a relatively narrow range of temperatures compared to temperatures naturally experienced by aquatic snails. However, our chosen testing temperatures lie well within the range of those of other experimental studies revealing a diet switch from animal prey to plant food in aquatic ectotherms, for instance a marine fish tested at 12-27°C (Behrens & Lafferty, 2007) and copepods tested at 10-24°C (Boersma et al, 2016). In both studies, the observed diet switch was also visible within the 15-25°C temperature range.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…We tested consumption rates and diet selection at three temperatures (15-25°C) which may be a relatively narrow range of temperatures compared to temperatures naturally experienced by aquatic snails. However, our chosen testing temperatures lie well within the range of those of other experimental studies revealing a diet switch from animal prey to plant food in aquatic ectotherms, for instance a marine fish tested at 12-27°C (Behrens & Lafferty, 2007) and copepods tested at 10-24°C (Boersma et al, 2016). In both studies, the observed diet switch was also visible within the 15-25°C temperature range.…”
Section: Discussionmentioning
confidence: 53%
“…One potential strategy to reduce the mismatch is to consume a diet with more carbohydrates which can be easily utilized for energy (Lee et al, 2015). This would imply selection for a more carbon-based diet with increasing temperatures and, hence, more plants and less meat for omnivorous ectotherms (Boersma et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sin embargo, en zonas tropicales con influencia de procesos de surgencia estacional, la variación temporal de la temperatura puede tener un intervalo de variación de entre 8 a 10 ºC en los primeros 50 m de profundidad (Giraldo et al, 2008;Rodríguez-Rubio & Giraldo, 2011;Valencia et al, 2013), como lo encontrado en nuestros resultados para Bahía Cupica. Estos dos parámetros oceanográficos generalmente influyen en la abundancia y el recambio de especies de copépodos, así como también, pueden modular la demanda metabólica, tasas de reproducción, talla, y preferencia alimentaria (Christou, 1998;Murcia & Giraldo, 2007;Rakhesh et al, 2013;Garzke, Ismar, & Sommer, 2015;Boersma et al, 2016;Horne, Hirst, Atkinson, Neves, & Kiørboe, 2016;Medellín-Mora et al, 2016). En nuestro caso es importante resaltar que la comunidad cambia en su estructura debido al efecto del ascenso de la termoclina y haloclina, producto de la influencia del proceso de surgencia de la Ensenada de Panamá.…”
Section: Discussionunclassified
“…As copepodites are slower growing and nearing reproduction, their survival may be maximized by adapting to higher temperatures and P limitation using phosphorus more efficiently according to the metabolic efficiency theory (Cross et al 2015; Boersma et al 2016). Because of the abundance and importance of P. crassirostris as a larval fish food source (Sampey et al 2007; Kline and Laidley 2015), changes in the survival, growth, and stoichiometry of this copepod species with climate change may alter subtropical coastal food webs.…”
Section: Introductionmentioning
confidence: 99%